2015
DOI: 10.1159/000381241
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Water Intake in Chronic Kidney Disease: Why? Safe? Possible?

Abstract: Increased water intake may slow the progression of chronic kidney disease by lowering vasopressin levels. Prior to initiating a large randomized controlled trial on the effect of increased water intake on renal decline, we conducted a six-week pilot study to examine the safety and feasibility of asking adults with chronic kidney disease to increase their water intake. We randomly assigned 29 patients to either a hydration or a control group. The hydration group was asked to increase water intake by 1 to 1.5 l/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It has been shown that ADC and fractional anisotropy (FA) values decrease with loss of renal function, which suggests their correlation with fibrosis in patients with CKD. It has been hypothesized that increasing water intake could slow down the progression of CKD . Alternatively, water intake may act as a confounder in determining renal stiffness, due to an increase in perfusion pressure, and affect the diagnosis of patients with renal pathologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ADC and fractional anisotropy (FA) values decrease with loss of renal function, which suggests their correlation with fibrosis in patients with CKD. It has been hypothesized that increasing water intake could slow down the progression of CKD . Alternatively, water intake may act as a confounder in determining renal stiffness, due to an increase in perfusion pressure, and affect the diagnosis of patients with renal pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that increasing water intake could slow down the progression of CKD. 31 Alternatively, water intake may act as a confounder in determining renal stiffness, due to an increase in perfusion pressure, and affect the diagnosis of patients with renal pathologies. Here, perfusion pressure refers to the resulting increased renal tubular pressure due to a decrease in the rate of water clearance from the renal tubules, caused by filling an entire volume of bladder after water intake.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, low water intake is associated with increased risk of developing hyperglycemia [ 4 ] and may increase the risk of developing type II diabetes [ 5 ]. Prospective studies measuring the impact of increased water intake on the development of these diseases are still in a preliminary phase [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these findings provide a rationale for intervention studies aiming to evaluate whether a reduction in AVP secretion or action could improve the metabolic status in people who are at risk of diabetes and have a high copeptin concentration/low hydration status. This may be achieved by moderate increase in water intake as it is actually tested for slowing progression of chronic kidney disease . Attention should be paid to the use of vaptan (V2 antagonist) because they induced secondarily an increase in water intake but also enhanced AVP secretion and thus V1aR‐mediated action.…”
Section: Resultsmentioning
confidence: 99%